Evaluating a Model by Forecast Performance. - Clements, M; Hendry, D (Blackwell Publishing, 2005)
Although out-of-sample forecast performance is often deemed to be the "gold standard" of evaluation, it is not in fact a good yardstick for evaluating models in general. The arguments are illustrated with reference to a recent paper by Carruth, Hooker and Oswald [Review of Economics and Statistics (1998), Vol. 80, pp. 621-628], who suggest that the good dynamic forecasts of their model support the efficiency-wage theory on which it is based.